Complications Associated with Posterior Cruciate Ligament Reconstruction and Avoiding Them - James, Evan W.; Taber, Caroline E.; Marx, Robert G. (The Journal of Knee Surgery, 2021)
Posterior cruciate ligament (PCL) injuries often occur as part of a multiligament injury pattern and can present a significant challenge to the treating surgeon. When PCL reconstruction is indicated, complications can arise in the intraoperative and postoperative period that lead to poor outcomes. These complications include neurovascular injury, fracture, compartment syndrome, persistent posterior laxity, motion loss, residual knee pain, osteonecrosis, and heterotopic ossification. The purpose of this review is to highlight complications associated with PCL reconstruction and strategies to avoid them.
Keywords: posterior cruciate ligament; posterior cruciate ligament reconstruction; complications; multiligament knee injury; compartment syndrome; heterotopic ossification; osteonecrosis